Splinted and Nonsplinted Crowns with Different Implant Lengths in the Posterior Maxilla by Three-Dimensional Finite Element Analysis. (3rd September 2018) - Lemos, Cleidiel Aparecido Araujo; Verri, Fellippo Ramos; Santiago Junior, Joel Ferreira; de Souza Batista, Victor Eduardo; Kemmoku, Daniel Takanori; Noritomi, Pedro Yoshito; Pellizzer, Eduardo Piza
Abstract : The aim of this study was to evaluate stress distribution in the implants/components and bone tissue for splinted and nonsplinted prostheses with different lengths of implants using three-dimensional finite element analysis. Six models from the posterior maxillary area were used in simulations. Each model simulated three Morse taper implants of 4.0 mm diameter with different lengths, which supported metal-ceramic crowns. An axial load of 400 N and an oblique load of 200 N were used as loading conditions. Splinted prostheses exhibited better stress distribution for the implants/components, whereas nonsplinted prostheses exhibited higher stress in the first molar under axial/oblique loading. Implant length did not influence stress distribution in the implants/components. In cortical bone tissue, splinted prostheses decreased the tensile stress in the first molar, whereas nonsplinted prostheses were subjected to higher tensile stress in the first molar; implant length had no influence on stress distribution. Within the limitations of this study, we conclude that splinted prostheses contributed to better stress distribution in the implant/abutment and cortical bone tissue; however, the reduction in the implant length did not influence the stress distribution.